(untitled) (Географический вестник=Geographical bulletin, 2017)
Дана оценка источников поступления биогенных веществ в Воткинское водохранилище. Рассмотрена динамика этих веществ по длине водоема, а также дана временная характеристика, в основу которой положены многолетние данные наблюдений за гидрохимическим режимом водохранилища. DYNAMICS OF NUTRIENTS IN VOTKINSKOE RESERVOIR The estimation of the sources of nutrients in the reservoir Votkinskoye. The dynamics of these substances on the length of the reservoir, also gives the time response, which builds on the long-term observations of hydrochemical regime of the reservoir.